Evaluasi Pengelolaan Obyek Wisata Air Panas Mamuya Kabupaten Halmahera Utara - Filus Raraga; Hersen F. Korengkeng (JURNAL DESTINASI PARIWISATA, 2021)
Tourism is a kind of activity which has multiplicative impact to economic development of a region especially moreover to society around the tourism place. Mamuya’s hot water spring is a tourist spot in North Halmahera Regency that have good prospectto develop. The purpose of this research is to study and evaluate development program of mamuya’s hot water spring by knowing public opinion about it. The method used in this study uses a Likert scale to find out the public opinion through a questionnaire then analyzed using SWOT analysis to compare people's opinions with the Mamuya hot water development program. The result shows that the necessity of promotion is very needed through somekind of tourism events as attraction to people; keeping the beauty of nature around the spot; repair and maintenance the access road to location; add the street light along the access road; repair the pool, add some more facilities as more toilets, more gazebos, shelter, umbrella houses, and keep the maintance; build some new facilities like provide the parking area, deposit counter, merchandise outlet (join with the craftsman round the place), building the awareness towards the importance of cleanliness; facilities development by local architecture; public facilities improvement as tourism supporting.Keywords: program, evaluation, hot, water spring, tourism